ANALISIS KEPUTUSAN KONSUMEN DALAM PEMBELIAN SMARTPHONE BERDASARKAN KUALITAS PRODUK, PROMOSI DAN DESAIN PRODUK - Tegowati Tegowati; Dewi Mutmainnah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The use of smartphones today is increasingly varied starting from the type, brand, price and quality offered. With the many alternative smartphone brands offered, it can support consumer decision making. Consumer decisions are certainly very important, because the determination of consumer decisions affects the continuity of a product in the market. This study aims to analyze promotion, product design and product quality on consumer purchasing decisions in Surabaya. This research data was collected through distributing questionnaires to 100 Samsung smartphone users in Surabaya using purposive sampling technique. The data analysis technique uses SEM AMOS 20. This study concludes that quality influences consumer decisions in purchasing smartphones, while product design and promotions do not affect consumer decisions in purchasing smartphones.